2020
DOI: 10.1038/s41467-020-15735-6
|View full text |Cite
|
Sign up to set email alerts
|

Aquaculture at the crossroads of global warming and antimicrobial resistance

Abstract: In many developing countries, aquaculture is key to ensuring food security for millions of people. It is thus important to measure the full implications of environmental changes on the sustainability of aquaculture. We conduct a double meta-analysis (460 articles) to explore how global warming and antimicrobial resistance (AMR) impact aquaculture. We calculate a Multi-Antibiotic Resistance index (MAR) of aquaculture-related bacteria (11,274 isolates) for 40 countries, of which mostly low-and middle-income coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
200
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 352 publications
(206 citation statements)
references
References 58 publications
2
200
0
4
Order By: Relevance
“…Despite the important role of aquaculture, the sector faces numerous challenges that hamper its expansion. Aquatic animal diseases are considered to be one of the major limiting factors for aquaculture development (Stentiford et al 2012(Stentiford et al , 2017, with increasing global trade, intensification of systems and climate change contributing to the emergence of infectious diseases (Karvonen et al 2010;Perry et al 2013;Reverter et al 2020). With high culture densities, intensified systems of production facilitate the evolution and spread of more virulent pathogens and the occurrence of disease outbreaks due to stressed and immuno-compromised animals (Bondad-Reantaso et al, 2005;Pulkkinen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the important role of aquaculture, the sector faces numerous challenges that hamper its expansion. Aquatic animal diseases are considered to be one of the major limiting factors for aquaculture development (Stentiford et al 2012(Stentiford et al , 2017, with increasing global trade, intensification of systems and climate change contributing to the emergence of infectious diseases (Karvonen et al 2010;Perry et al 2013;Reverter et al 2020). With high culture densities, intensified systems of production facilitate the evolution and spread of more virulent pathogens and the occurrence of disease outbreaks due to stressed and immuno-compromised animals (Bondad-Reantaso et al, 2005;Pulkkinen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The review included data from 40 countries, which account for 93% of the global animal aquaculture production. Twenty-eight countries out of the 40 studied displayed MAR indices higher than 0.2, a threshold considered to be an indication of high-risk antibiotic contamination [189].…”
Section: Agriculture and Aquaculturementioning
confidence: 99%
“…Aquaculture systems have become genetic hotspots for gene transfer in seawater bacteria due to the mixing of feed combinations, which include antibiotics, probiotics, and prebiotics [186][187][188]. A systematic literature review and meta-analysis found that the multi-antibiotic resistance (MAR) index of aquaculture-related bacteria correlates with MAR indices from human clinical bacteria [189]. The review included data from 40 countries, which account for 93% of the global animal aquaculture production.…”
Section: Agriculture and Aquaculturementioning
confidence: 99%
“…The dearth of studies addressing these types of questions in New Zealand is obvious. Empirical data is needed because the effect of temperature on disease is not uniform; for example, the haplosporidian B. ostreae prefers cooler more saline waters (Arzul et al 2009), whereas incidences of bacterial infection across multiple aquaculture species have increased with warmer waters (Reverter et al 2020). The collection of empirical data of host-parasite interactions under different environmental conditions allows for more accurate forecasting of disease risks and a clearer prioritisation of future research effort to mitigate those risks.…”
Section: Effect Of Climate Change On Parasitic Diseasesmentioning
confidence: 99%